Evaluation of the vestibular system in individuals with presbycusis using video head impulse test and videonystagmography. (1st June 2021) - Say, Mehmet Ali; Sevik Elicora, Sultan; Erdem, Duygu; Bilgin, Ergin; Baklaci, Deniz
Abstract: Background: Vestibulo-ocular reflex (VOR) function is expected to be normal in patients with presbycusis during sudden head rotations. Aim: This study aimed to determine whether presbycusis was accompanied by vestibular system pathologies. In addition, it was examined whether there was a difference existed between the patients with and without presbycusis in terms of normative data. Materials and Methods: A total of 40 individuals were included in the study: 20 in the presbycusis group and 20 in the control group. The vestibular systems of both groups were evaluated using the video head impulse test and videonystagmography. Results: The right and left lateral VOR gain values were decreased in the group with presbycusis compared to the control group. The difference between the two groups in the mean VOR gains in the right lateral canal and left lateral canal were statistically significant ( p  = .040 and p  = .050, respectively). The air caloric tests of all individuals were found to be normal. Conclusions: This result suggests that the loss of vestibular hair cells and vestibular nerve degeneration in the lateral semicircular canal may be more severe in presbycusis than in the same age group with normal hearing.